Early Comprehensive Kidney Care in Dialysis-Requiring Acute Kidney Injury Survivors: A Populational Study - Wu, Chun-Yi; Liu, Jia-Sin; Chen, Cheng-Hsu; Huang, Chun-Te; Yu, Tung-Min; Chuang, Ya-Wen; Huang, Shih-Ting; Hsu, Chih-Cheng; Wu, Ming-Ju (Frontiers in Medicine, 2022)
Background For patients with Acute Kidney Injury (AKI), a strong and graded relationship exists between AKI severity and mortality. One of the most severe entities of AKI is Dialysis-Requiring Acute Kidney Injury (D-AKI), which is associated with high rates of mortality and end-stage renal disease (ESRD). For this high-risk population group, there is a lack of evidence regarding optimal post-AKI care. We propose that post-AKI care through the combined efforts of the nephrologist and the multidisciplinary care team may improve outcomes. Our aim here is to study for survivors of dialysis-requiring acute kidney injury, the effects of implementing early comprehensive kidney care.. Methods This is a retrospective longitudinal cohort study of Taiwanese through analyzing the National Health Insurance Research Database (NHIRD). We included patients with acute dialysis during hospitalization from January 1, 2015 to December 31, 2018. Propensity match was done at 1:1, including estimated glomerular filtration rate (eGFR) based on CKD-EPI which was performed due to large initial disparities between these two cohorts. Results After the propensity match, each cohort had 4,991 patients. The mean eGFR based on CKD-EPI was 27.5 ml/ minute/1.73 m2, and the mean follow-up period was 1.4 years. The hazard ratio for chronic dialysis or ESRD was 0.55 (95% CI, 0.49 to 0.62; p <0.001). The hazard ratio for all-cause mortality was 0.79 (95% CI, 0.57 to 0.88; p <0.001). Both outcomes favored early comprehensive kidney care. Conclusions For survivors of dialysis-requiring acute kidney injury, early comprehensive kidney care significantly lowered risks of chronic dialysis and all-cause mortality.